Peran Pendidikan Agama Islam dalam Membentuk Karakter Kejujuran Sejak Usia Dini pada TK Aisyiyah 2 Pasui Kabupaten Enrekang - Hasm; Raya Mangsi; Suraedah Hamid; St.Wardah Hanafie Das; Muhammad Naim (Jurnal Ragam Pengabdian, 2026)
This thesis discusses; a. How is the implementation of Islamic Religious Education in Aisyiyah Kindergarten 2 Pasui Enrekang Regency? b. How does the impact of Islamic Religious Education Learning methods on the formation of character honesty early childhood in kindergarten Aisyiyah 2 Pasui Enrekang? c. How is the strategy of optimizing the role of Islamic Religious Education in shaping the character of honesty from an early age in Aisyiyah Kindergarten 2 Pasui Enrekang Regency? the purpose of this study is to a. To describe the implementation of Islamic Religious Education in kindergarten Aisyiyah 2 Pasui Enrekang. b. To assess the impact of the impact of Islamic Religious Education Learning methods on the formation of character honesty early childhood in kindergarten Aisyiyah 2 Pasui Enrekang. c. To identify the optimal strategy in improving the role of Islamic Religious Education in shaping the character of cruelty in early childhood in Aisyiyah Kindergarten 2 Pasui Enrekang Regency. As a complement to this thesis, the author uses a qualitative type of research with a methodological, theoretical and pedagogical approach. The study was conducted for 3 months in kindergarten Aisyiyah 2 Pasui Enrekang. primary data sources are; principals, teachers, and operators, while secondary data sources are; school data, articles, journals, and others with data collection techniques; observation, interviews and documentation. With analytical techniques; data reduction, data presentation and conclusion. Test the validity of the data used; Credibility, Transferability, dependability, and confirmability. The results of this study indicate, in conclusion, Islamic Religious Education in kindergarten Aisyiyah 2 Pasui Enrekang has a very strategic role in shaping the character of honesty in early childhood through fun, interactive, and experience-based learning, such as stories of the Prophet, prayer together, and role-playing games. The implementation of religious values integrated in daily activities, supported by the example of educators and a safe learning atmosphere, is able to foster an honest attitude in children naturally according to their stage of development. The success of this character formation is more optimal with the involvement of parents, the use of applicable methods, and structured evaluations, so that the value of honesty is not only embedded in the school environment, but also consistently applied in children's daily lives..